Hydrogen crossover through perfluorosulfonic acid membranes with variable side chains and its influence in fuel cell lifetime - Zhang, Huijie; Li, Junsheng; Tang, Haolin; Lin, Yu; Pan, Mu (International journal of hydrogen energy, 2014)
In this study, hydrogen crossover in long side chain Nafion 211 membrane and short side chain Aquivion membrane is studied under different conditions. It is found that both temperature and relative humidity significantly influence the hydrogen crossover in the polymer electrode membranes (PEMs). The difference in hydrogen crossover behavior between Nafion 211 membrane and Aquivion membrane is revealed. The influence of hydrogen crossover on the fuel cell lifetime is also investigated under open circuit voltage (OCV). It is proved hydrogen crossover in the PEM would lead to possible degradation of the PEM and the decrease of electro-chemical surface area in the catalyst of the single cell. Single cell assembled with Aquivion membrane shows slower OCV and ECSA decay compared to the Nafion 211 single cell. Our results suggest that the PEM fuel cell lifetime is closely related to the hydrogen crossover in the PEM. The current study also highlights the possibility of improving the fuel cell durability by rational design of the PEM morphology.